Caring Ditinjau Dari Tipe Kepribadian Studi Pada Perawat Di RSJD Atma Husada Mahakam Samarinda - ., Syahputri . (MOTIVASI, 2013)
ABSTRACTThis study aims to determine the differences between nurses caring extrovert and introvertpersonality type in RSJD Atma Husada Mahakam Samarinda. The hypothesis of this study is thatthere is a positive relationship between the type kpribadian Caring extrovert and introvert.The population in this study were all nurses who work in RSJD pungsional Atma HusadaMahakan Samarinda which numbered 119 people. While the sample in this study were 73 nursesfunctional. The data revealed by research nurses using a scale and scale Caring personalitytype. Data analysis techniques used to reveal the differences and the nurses caring personalitytype using the t-test.Based on the analysis conducted obtained t = 1.771, p= 0.081 (p <0.05) that means there is nodifference between nurse caring extrovert and introvert personality type. Which means that thehypothesis is rejected because of the results of the study of personality types contribute only 8%of the nurses caring. While 92% are influenced by other factors.